2014
DOI: 10.1016/j.eururo.2014.05.034
|View full text |Cite
|
Sign up to set email alerts
|

Cytoreductive Nephrectomy in Patients with Synchronous Metastases from Renal Cell Carcinoma: Results from the International Metastatic Renal Cell Carcinoma Database Consortium

Abstract: We looked at the survival outcomes of metastatic renal cell carcinoma patients who did or did not have the primary tumor removed. We found that most patients benefited from tumor removal, except for those with four or more IMDC risk factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

24
279
0
19

Year Published

2016
2016
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 420 publications
(322 citation statements)
references
References 17 publications
24
279
0
19
Order By: Relevance
“…These patients have a poor outcome, which is supported by retrospective series and prognostic scoring systems 4,5 . There is also uncertainty about the role and timing of nephrectomy.…”
Section: Discussionmentioning
confidence: 89%
See 4 more Smart Citations
“…These patients have a poor outcome, which is supported by retrospective series and prognostic scoring systems 4,5 . There is also uncertainty about the role and timing of nephrectomy.…”
Section: Discussionmentioning
confidence: 89%
“…These patients had a poor outcome irrespective of whether they had surgery (median overall survival <6 months, eFigure 2). Previous retrospective analysis of other smaller prospective series with sunitinib suggested that nephrectomy was not recommended in this setting 4,15 . Our data supports this recommendation with the most robust data to date.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations